Techno-economic assessment at full scale of a biogas refinery plant receiving nitrogen rich feedstock and producing renewable energy and biobased fertilisers. (25th July 2021) - Brienza, C.; Sigurnjak, I.; Meier, T.; Michels, E.; Adani, F.; Schoumans, O.; Vaneeckhaute, C.; Meers, E.
Abstract: Anaerobic digestion of nitrogen (N) rich substrates might be hindered when ammonia (NH3 ) formation reaches toxic levels for methanogenic microorganisms. One possible strategy to avoid inhibiting conditions is the removal of NH3 from digestate by stripping and scrubbing technology and by recirculating N depleted digestate back to the digester. This study aimed to i) monitor the performance (mass and energy balances) of a full scale digestate processing cascade that includes an innovative vacuum side stream NH3 stripping and scrubbing system, ii) assess the production cost of ammonium sulphate (AS) solution and iii) evaluate its fertiliser quality. The use of gypsum to recover NH3 in the scrubbing unit, instead of the more common sulphuric acid, results in the generation of AS and a fertilising liming substrate. Mass and nutrient balances indicated that 57% and 7.5% of ammonium N contained in digestate was recovered in the form of a 22% AS and liming substrate, respectively. The energy balance showed that about 3.8 kWhel and 59 kWhth were necessary to recover 1 kg of N in the form of AS. Furthermore, the production cost of AS, including both capital and operational costs, resulted to be 5.8 € t −1 of digestate processed. According to the fertiliser quality assessment, this technology allows for the recovery of NH3 in the form of salt solutions that can be utilised as a substitute for synthetic mineral nitrogen fertilisers. Highlights: A novel ammonia stripping process was monitored at a fullscale digestate processing facility. 57% of ammonium nitrogen contained in digestate was recovered as ammonium sulphate (22%). Nitrogen in recovered ammonium sulphate is present entirely in mineral form. The cost for the nitrogen recovery system amounts to 5.8 € per tonne of digestate processed. Biobased ammonium sulphate represents an interesting alternative to synthetic nitrogen fertilisers.